Rough night - Aniello, Lucia; Johansson, Scarlett, 1984-; McKinnon, Kate, 1984-; Bell, Jillian, 1984-; Lewis, Dominic (Culver City, California : Sony Pictures Home Entertainment, 2017)
Things go awry when a group of college friends reunite for a bachelorette party in Miami.
Originally released as a motion picture in 2017.
Dolby digital 5.1, wide screen 2.39:1.
Features: Dynamic duo : Lucia and Paul, Scandalous sing-a-long, Do a little dance, Improv-a-rama.
Cinematographer, Sean Porter ; editor, Craig Alpert ; music, Dominic Lewis.
Scarlett Johansson, Kate McKinnon, Jillian Bell, Ilana Glazer, Zoë Kravitz.
MPAA rating: R.
Keywords: Bachelorette parties -- Drama; Male strippers -- Drama; Death -- Drama; Friendship -- Drama; Dark comedy films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Feature films; Comedy films